ANALISIS PENGARUH PROMOSI, HARGA, DAN KUALITAS PELAYANAN TEHADAP MINAT PELANGGAN MENGGUNAKAN JASA LOGISTIK PADA PT. MONANG SIANIPAR ABADI KARGO SEMARANG - Sufriyano Sufriyano; Retno Mulatsih (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
To be able to attract customers companies apply different approaches but when viewed from the factors that influence consumer buying decisions on a product both goods and services the consumer behavior approach system is shown in searching, buying, using, evaluating, and spending products and services that they expect to satisfy their needs, Kanuk & Schiffman (2010). This study aims to determine and analyze the factors that influence customer interest in using logistics services at PT Monang Sianipar Abadi Kargo Semarang. To achieve this goal descriptive research was conducted using the methods of observation, in-depth interviews, literature study, documentation, and questionnaires. The results showed that sales promotion, building relationships with the community, direct marketing, price affordability, price competitiveness, price compatibility with service quality, service in accordance with customer requests, speed of document service and the ease with which customers can obtain information and respond to customer complaints will give a positive impression of each customer has a positive and significant effect on attracting customers to use logistics services at PT. Monang Sianipar Abadi Kargo Semarang.